Affiliations for homeless individuals through social enterprise employment. Issue 2 (16th April 2019) - Cook, Molly; Willetts, Marion C.
Abstract : Purpose: This paper aims to explore the ways in which a social enterprise provides opportunities to its homeless employees to increase their number and types of affiliations. Design/methodology/approach: Affiliation theory is used to explore whether employment at a social enterprise may ameliorate homelessness by increasing the affiliations employees acquire. Seven semi-structured in-depth interviews were conducted with participants at one social enterprise. Findings: Results indicate that enterprise leadership staff facilitate opportunities to employees to increase and maintain their affiliations. Leadership staff provide a supportive environment, allowing employees to gain social skills and feelings of utility that result in their building and maintaining affiliations. However, leadership staff confront high turn-over, addiction and mental illness among employees, which result in disaffiliation. Employees contend with a lack of housing and limited educational and job training opportunities; obtaining these resources in the future may necessitate additional affiliations. Originality/value: This paper contributes to the current state of knowledge concerning affiliation theory and the employment of homeless individuals through a social enterprise by demonstrating the importance of both strong and weak ties between employees and employers, social service agencies, other employees and members of the community outside of work, and how the strength of ties may change over time.